CONVERGENCE TO IND AS: AN INVESTIGATION OF FACTORS AFFECTING PERCEPTION OF CHARTERED ACCOUNTANTS (IITM Journal of Business Studies, 2024)
In recent years, business has gotten increasingly  difficult, and a globalised market requires  comprehensive Accounting Standards that  can be applied equally and promote fairness  across corporations and regions. In the age of  globalisation, India needs and wants Ind AS.  With the introduction of IFRS globally, there  was an urgent need to have similar standards for  India as well. Therefore, Ind AS were converged  with IFRS in 2011. Ind AS were made applicable  in India from April 2015 voluntarily and then  in a phased manner it was made mandatory  from April 2016. The present study focusses on  finding the factors affecting the perception of  Chartered Accountants in India regarding the  adoption of Ind AS. Primary data was collected  on structured Likert scale questionnaire and data  was analysed using Smart PLS 4. The findings of  the study revealed that challenges and limitation  have a negative impact on the perception while  utilities, training and development of common  understanding have a positive impact. Adoption  process was found to be insignificant.
Keywords: Ind AS; IFRS; Utilities; Perception; Adoption Process; Challenges; Limitations; Development of Common Understanding; Training.